Synergistically improved thermal conductivity of polyamide-6 with low melting temperature metal and graphite - Y. C. Jia; H. He; P. Yu; J. Chen; X. L. Lai (eXPRESS Polymer Letters, 2016)
Low melting temperature metal (LMTM)-tin (Sn) was introduced into polyamide-6 (PA6) and PA6/graphite composites respectively to improve the thermal conductivity of PA6 by melt processing (extruding and injection molding). After introducing Sn, the thermal conductivity of PA6/Sn was nearly constant because of the serious agglomeration of Sn. However, when 20 wt% (5.4 vol%) of Sn was added into PA6 containing 50 wt% (33.3 vol%) of graphite, the thermal conductivity of the composite was dramatically increased to 5.364 versus 1.852 W·(m·K)–1 for the PA6/graphite composite, which suggests that the incorporation of graphite and Sn have a significant synergistic effect on the thermal conductivity improvement of PA6. What is more, the electrical conductivity of the composite increased nearly 8 orders of magnitudes after introducing both graphite and Sn. Characterization of microstructure and energy dispersive spectrum analysis (EDS) indicates that the dispersion of Sn in PA6/graphite/Sn was much more uniform than that of PA6/Sn composite. According to Differential Scanning Calorimetry measurement and EDS, the uniform dispersion of Sn in PA6/graphite/Sn and the high thermal conductivity of PA6/graphite/Sn are speculated to be related with the electron transfer between graphite and Sn, which makes Sn distribute evenly around the graphite layers.